Effects of uncoordinated electrification on energy burdens for natural gas customers - Jaime Garibay-Rodriguez; Morgan R. Edwards; Ann F. Fink; Zeyneb Magavi (Scientific Reports)
Abstract Electrification presents opportunities and challenges for household energy affordability. Without careful coordination, the costs of natural gas systems will be borne by a shrinking customer base, driving up bills for those left behind. This affordability issue is worsened by new pipeline investments, which risk locking communities into increasingly expensive infrastructure. Here, we introduce a framework to quantify the effects of uncoordinated electrification on natural gas customers, integrating household energy data with utility financial and planning documents. Applying our framework first to Massachusetts and then nationwide, we show that vulnerable communities face disproportionate affordability risks during heating electrification transitions. Households that do not electrify may bear a 46% increase in gas bills on average over the next 15 years (relative to current costs). Targeted electrification may help to alleviate energy burdens, but an effective heating transition will ultimately require coordinated, neighborhood-scale strategies that consider the high fixed costs of legacy infrastructure.